Shopping Model on Traditional Online Market - Kurniati, Rini Rahayu; Afifuddin, Afifuddin; Ewaldy, Silvio Maric (International Journal of Artificial Intelligence Research, 2022)
This study aims to analyze the shopping model during the Covid-19 pandemic and the role of shopping models in traditional online markets for consumers in traditional online markets in Malang City. This study was a descriptive qualitative method. Data were collected by using technical triangulation through Hyarta Danadipa Raya company and online traditional market consumers as informants. The shopping model at the traditional online market in Malang city used the Tumbasin application. It was accessible by following the two steps to pay online. Moreover, it could be processed directly by the online market service. Within half to one hour, the goods could be received by consumers. The role of the shopping model in traditional online markets provided convenience, fast service, appropriate services according to orders, convenience in payments and security during the Covid-19 pandemic.Â Â